Entre la alucinación y la realidad: El caso 117.720 de Carmen Naranjo Coto. - Vallejos Ramírez, Mayela (2012)
The main objective of this paper is to disentangle the essence of Carmen Naranjo's novel El caso 117.729. This extraordinary novel expounds the reality of a society that is disintegrating, vanishing, and rotting, similar to the main character of the novel. This man is fighting a terrible mental and physical illness that no doctor knows how to treat. The technique that the author uses to expose her points of view is what makes it very unique. The structure is fragmented; however, the plot does not lose its coherence.